Propuesta de estrategia de internacionalización a través de plataformas digitales para el sector turístico de villa de Leyva- Boyacá (2021)
The municipality of Villa de Leyva located in the Department of Boyacá is considered one of the most important tourist spots in the country. Declared a National Monument in 1954, the municipality has relevant sites such as the main square, which is not only the largest in Colombia, but one of the largest in South America; several paleontological museums that house dinosaur fossils found in the zone and blue wells immersed in the desert area. It is a place where its historical importance, preserved colonial architecture and natural diversity give it great cultural charm and an even greater tourist attraction (Colombia Travel, 2021).